Variability of soil surface characteristics in a mountainous watershed in Valle del Cauca, Colombia: Implications for runoff, erosion, and conservation - Guzmán, Christian D.; Hoyos Villada, Fanny; Silva, Mayesse Aparecida da; Zimale, Fasikaw A.; Chirinda, Ngonidzashe; Botero, César; Morales Vargas, Amalia; Rivera, Baudelino; Moreno, Pedro; Steenhuis, Tammo S. (Elsevier, 2019)
Understanding catchment sediment or solute transport frequently relies on understanding of soil nutrient conditions and physical properties. This study investigates hydropedological patterns in a tropical catchment by understanding soil nutrient and soil surface changes. Soil nutrient concentrations and hydraulic properties were measured from the La Vega micro watershed in the southwestern Colombian Andes at 16 distributed locations in four elevation ranges (between 1450 and 1700 m a.s.l.). The site is a part of a conservation partnerships which implements programs and monitor impacts. Soil samples were analyzed for total nitrogen (TN), Bray II-available phosphorus, exchangeable cations, pH, organic matter, and texture. Soil hydraulic conductivities at two depths (0–5 cm and 5–10 cm) were determined in conservation implementation areas (enclosures and natural regrowth). In the upper elevation range, regrowth of natural vegetation was found on deep soils (∼3 m) with moderate infiltration (26 cm hr−1), the lowest bulk density (0.92 g cm−3), and the highest TN (0.4%). The lowest elevation (mixed land use of grazing and riparian forests with deep profiles) had the lowest infiltration (4 cm hr−1), highest bulk density (1.02 g cm−3), and the lowest TN (0.26%). In the middle elevation ranges, conserved tropical forest vegetation were located on shallow soil depths with high organic matter (∼6%) and high infiltration (86 cm hr−1). The lowest infiltration rate average (2.3 cm hr−1) exceeded the estimated erosive regional precipitation intensity (∼2.5 cm hr−1) about 60% of the time, while the median infiltration rate (10 cm hr−1) exceeded rainfall intensities 94% of the time, indicating that infiltration excess and saturation excess runoff mechanisms are both present. Coupling data with sediment concentration and solute concentration patterns can help discern correlations between scales and will help to monitor effectiveness of conservation programs aimed at sustaining ecosystem services.